2010
DOI: 10.1186/1471-2180-10-230
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of secreted proteins of Propionibacterium acnes

Abstract: BackgroundThe anaerobic Gram-positive bacterium Propionibacterium acnes is a human skin commensal that resides preferentially within sebaceous follicles; however, it also exhibits many traits of an opportunistic pathogen, playing roles in a variety of inflammatory diseases such as acne vulgaris. To date, the underlying disease-causing mechanisms remain ill-defined and knowledge of P. acnes virulence factors remains scarce. Here, we identified proteins secreted during anaerobic cultivation of a range of skin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
158
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(174 citation statements)
references
References 59 publications
6
158
0
6
Order By: Relevance
“…Furthermore, free glycerol released from sebum by lipase may act as an important carbon source and, along with the potential nutritional role also played by neuraminidase, promote growth (McGinley et al, 1980;Corfield, 1992). The demonstration of differences in the expression of dermatan-sulphate-binding proteins in this study and others (Lodes et al, 2006;Holland et al, 2010), and the observation of probable phase variation within type IA strains are likely to prove to be important observations in the context of acne pathogenesis, particularly as dermatan sulphate is the predominant glycosaminoglycan in skin and a biological response modifier involved in processes such as cytokine activity and wound repair.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, free glycerol released from sebum by lipase may act as an important carbon source and, along with the potential nutritional role also played by neuraminidase, promote growth (McGinley et al, 1980;Corfield, 1992). The demonstration of differences in the expression of dermatan-sulphate-binding proteins in this study and others (Lodes et al, 2006;Holland et al, 2010), and the observation of probable phase variation within type IA strains are likely to prove to be important observations in the context of acne pathogenesis, particularly as dermatan sulphate is the predominant glycosaminoglycan in skin and a biological response modifier involved in processes such as cytokine activity and wound repair.…”
Section: Discussionmentioning
confidence: 76%
“…Expression of neuraminidase and lipase (GehA) appears to be especially associated with type IA isolates, and the production of lipase in particular is believed to play an important role in the pathophysiology of acne (Lomholt & Kilian, 2010;Holland et al, 2010). This is due to the release of glycerol and free fatty acids from sebum triglycerides which may be inflammatory and chemotactic, and promote ductal hypercornification and adhesion between P. acnes and the hair follicle (Gribbon et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…or proteases that may inactivate or inhibit complement (54)(55)(56)(57). It is also possible that sMAC levels in this cohort are depressed, in part, due to complement depletion, as reported in S. epidermidis infections in ventriculoatrial shunt patients (23); however, this seems less likely, as sMAC is stable relative to other complement activation products (58).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 54%
“…The bacterium has an overall clonal structure, and its isolates can be classified into a number of statistically significant clades or phylogroups designated types IA 1 , IA 2 , IB, IC, II, and III; these types appear to display differences in their associations with specific types of infections (20,21) and vary in their production of putative virulence determinants (19,20,(29)(30)(31)(32), inflammatory potential (33)(34)(35)(36), antibiotic resistances (21,37), aggregative properties (16), and morphological characteristics (19). In particular, a number of independent epidemiological studies have shown a strong association between clonal complexes from the type IA 1 phylogroup and moderate-to-severe acne, while the lineages from all other phylogroups appear more frequently to be isolated from medical device and soft tissue infections or be associated with health as true commensals (20,21,31,38).…”
mentioning
confidence: 99%